Recent Synthesis of Mono- & Bis-Pyranopyrazole Derivatives - Saba, Farooq; Zainab, Ngaini (Wiley-VCH GmbH, Weinheim, 2024)
Pyranopyrazole is an important structural unit in heterocyclic chemistry and is useful in pharmaceutical and agrochemical industries. The pyranopyrazole-based compounds are known in the agricultural industry as herbicides, fungicides, and insecticide agents and in medicinal fields as antimicrobial, anticancer, and antiHIV agents. Despite its wide range of applications, the synthesis of pyranopyrazole has several limitations such as the cost of reagents, potential environmental risks, harsh reaction conditions, longer reaction times, laborious workup procedures, and unsatisfactory yields. However, many studies have been recently reported on the synthesis of pyranopyrazoles using mild, green, and environmentally friendly methods that also give higher yields. Different catalysts and conditions have been reported for the synthesis of pyranopyrazole using four, three, and two components. Among these, four-component synthesis is commonly reported by using benzaldehyde, hydrazine derivatives, ethyl acetoacetate and malononitrile due to the commercial availability and stability of the reagents. This review summarized the recent synthesis of pyranopyrazole i. e., mono- and bis-pyranopyrazole derivatives via four-, three- and two-component-based reactions. Mono- and bis-pyranopyrazole derivatives varied due to the number of pyranopyrazole units that contributed to play an important role in increasing the binding interaction and biological activities beneficial for pharmaceutical industries.